Efficiency of the energy contained in modulators in the Arabic vowels recognition - Nesrine Abajaddi; Youssef Elfahm; Badia Mounir; Laila Elmaazouzi; Ilham Mounir; Abdelmajid Farchi (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The speech signal is described as many acoustic properties that may contribute differently to spoken word recognition. Vowel characterization is an important process of studying the acoustic characteristics or behaviors of speech within different contexts. This current study focuses on the modulators characteristics of three Arabic vowels, we proposed a new approach to characterize the three Arabic vowels /a/, /i/ and /u/. The proposed method is based on the energy contained in the speech modulators. The coherent subband demodulation method related to the spectral center of gravity (COG) was used to calculate the energy of the speech modulators. The obtained results showed that the modulators energy help characterize the Arabic vowels /a/, /i/ and /u/ with an interesting recognition rate ranging from 86% to 100%.